Methodological pluralism in economics - Wojciechowska, Renata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The purpose of the paper is to analyse the issue of a test method in economics. It calls for the necessity of adopting a methodological approach that will be flexible and cognitively inspiring, which is a prerequisite to establishing the foundations for economics, its development and effectiveness in clarifying social and economic phenomena. Currently believed to be a complex (both theoretical and empirical), and inductive-deductive science, economics fails to possess binding methodological arrangements. Therefore, when looking for good solutions, scholars propose universal pluralism, which lets them expand the research apparatus within defined, yet not tightly logical structures
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 489, s. 474-482
Keywords: methodology of economics; philosophy of economics; metaeconomics; test method; methodological pluralism; metodologia ekonomii; filozofia ekonomii; metaekonomia; metoda badawcza; pluralizm metodologiczny